The third screen the ultimate guide to mobile marketing - Martin, Chuck 1949- (Brealey, 2015)
""Anyone interested in the evolution of consumer behavior and the adoption of new technologies will appreciate the clarity of Martin's prose and the breadth of his vision."...Publishers Weekly"Marketing is ever-changing and The Third Screen mirrors the future of marketing. If you are new to mobile, this book makes sure you get it right!"...Jeffrey Hayzlett, best-selling author of The Mirror Test"Chuck Martin has more than all the facts. He has the soul of the idea. The Third Screen is thoughtful and valuable."...Chris Brogan, president, Human Business Works, co-author of Trust AgentsIn this fully updated new edition, Chuck Martin updates his essential marketing handbook for a rapidly evolving mobile marketplace. With more than one in every five people owning a smart phone or tablet worldwide, companies that fail to market to their ecommerce customers will be left behind. The book covers mobile video, SMS (text) messaging, location-based marketing, advertising and media, and inbound marketing and offers insightful case studies of top companies who are using these new platforms successfully.Chuck Martin is director of the Center for Media Research at MediaPost Communications, a research firm that analyzes the intentions of media buyers and planners. He is also CEO of Mobile Future Institute, a US-based think tank focused on marketing tactics for a world gone mobile. Martin is the author of eight business books, including the New York Times business bestseller The Digital Estate. He has appeared on CNN, CNBC, Fox, and ABC-TV News Now. "..
Keywords: BUSINESS & ECONOMICS / Marketing / General; BUSINESS & ECONOMICS / E-Commerce / Internet Marketing; BUSINESS & ECONOMICS / Advertising & Promotion; COMPUTERS / Electronic Commerce (see also headings under BUSINESS & ECONOMICS / E-Commerce); Unternehmen; Wirtschaft; Telemarketing; Internet marketing; Mobile commerce; Smartphones; Internet advertising; Business enterprises -- Computer networks; Online-Marketing; Marketing; Smartphone